Magahiya Doms and untouchability - Verma, Sonali (The Indian Economic & Social History Review, 2024)
Magahiya Doms have historically suffered from the double stigma of criminality and untouchability. They were notified as a Criminal Tribe in 1913 but also came to be recognised as useful for the colonial state due to their role as sweepers and scavengers. The missionaries and colonial officials attempted to order and fix the identities of communities such as these. In this paper, I discuss the concept of touch and untouchability in relation to the caste system in India. I juxtapose the idea of the body proposed by Ambedkar in Annihilation of Caste against the caste body and colonised body. Against the static and closed identity which the state attempted to bestow on the Doms, I seek to understand the body itself as processual, moving and relational. Magahiya Doms resisted colonial moves to stabilise social identities every step of the way. I also discuss the role of the colonial apparatus as a mediator that sought to impose a new order of hygiene. The colonial mechanisms of governance cut off the older ties and relational tendencies and placed themselves and their logistics as chains through which frozen identities could communicate. In this way, they partitioned off bodies and settled themselves as chains connecting the partitioned bodies. After being de-notified as a Criminal Tribe, the Magahiya Doms were categorised as a Scheduled Caste in 1952.
Keywords: Body; Magahiya Doms; Touch; Untouchability; Caste